Identification of Physical Factors and Individual Characteristics Affecting The Event of Sick Building Syndrome (SBS) In Employees At The Class I Immigration Office of TPI Bandar Lampung - Anisa Adelia; Khairun Nisa Berawi; Dwita Oktaria; Winda Trijayanthi Utama (MAJORITY, 2023)
Sick Building Syndrome (SBS) is a collection of symptoms that can be experienced by someone who works in a building. A person is declared to have Sick Building Syndrome (SBS) if they have complaints of at least two or three symptoms of the total symptoms (eye irritation such as sore, red or watery eyes, throat irritation, pain when swallowing, itchy throat, sneezing, dry cough, shortness of breath, heaviness in chest, dry, red and itchy skin, nausea, fatigue, difficulty concentrating, drowsiness, dizziness). SBS can be enforced if the various complaints that exist are felt by around 20% -50% of users of a building, and these complaints disappear when workers leave the building. This study was an observational analytic study with a cross sectional design. The sampling technique used was total sampling with a minimum sample size of 63 people. Data were collected using the The Miljo-Medicin 040 Questionnaires (MM040EA) questionnaire for individual characteristics and symptoms of SBS and direct measurements for physical factors. Data analysis used chi square test and logistic regression test. Based on the data obtained the p value of each variable which states a relationship, namely gender (0.102), age (0.028), length of work (0.002), smoking habits (0.006), psychosocial conditions (0.007), air flow rate (0.029 ), lighting (0.042). The results of the multivariate analysis test showed that the length of work variable was the most dominant factor on SBS with a p value (0.015). The variables that affect the incidence of SBS are age, length of work, smoking habits, psychosocial conditions, air flow rate, lighting and the most dominant variable is length of work.